2017
DOI: 10.1039/c7ra02161e
|View full text |Cite
|
Sign up to set email alerts
|

Fractal analysis of pre-reduced Pt/TiO2catalysts for formaldehyde oxidation

Abstract: The amount of reactive sites, usually dispersed noble atoms, on the top of a catalyst rough surface is characterized within the framework of fractal geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…4,5 Extensive research on HCHO oxidation at room temperature has been conducted recently, with principal technologies using noble-metal-supported catalysts. [6][7][8][9][10][11] Zhang et al reported that HCHO could be completely oxidized to CO 2 over a Pt/TiO 2 catalyst, and they performed diffuse reectance infrared Fourier transform spectroscopy (DRIFTS) to propose a reaction model. 12 In this model, differences in catalytic activity were caused by the specic intermediate products produced, including CO and formate species.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Extensive research on HCHO oxidation at room temperature has been conducted recently, with principal technologies using noble-metal-supported catalysts. [6][7][8][9][10][11] Zhang et al reported that HCHO could be completely oxidized to CO 2 over a Pt/TiO 2 catalyst, and they performed diffuse reectance infrared Fourier transform spectroscopy (DRIFTS) to propose a reaction model. 12 In this model, differences in catalytic activity were caused by the specic intermediate products produced, including CO and formate species.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Fractal analysis, with inherent irregularity and complexity, can explain the variation in reactivity of many heterogeneous catalytic processes. 12,13 The effect of irregular catalyst pore fractal structure on the diffusive transport 14 and reaction in a porous media 15 catalysis, such as the percolation model, 16 the stochastic pore network model, 17 and the pore network-continuum model. 18 The fractal geometrical description of the pore networks is given for diffusion-limited aggregation (DLA) clusters, 19 regularly symmetric fractal structures, 20 and statistically symmetric fractal percolating pore networks.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous catalysis, where reactant and catalyst separated in different phases, can be quite different from its homogeneous equivalent, because the diffusion and reactions are restricted to porous catalyst fractal space with <3 dimensions, so the mobility restricts the rate. Fractal geometry is an essential part of the characterization of catalysts. , Fractal analysis, with inherent irregularity and complexity, can explain the variation in reactivity of many heterogeneous catalytic processes. , The effect of irregular catalyst pore fractal structure on the diffusive transport and reaction in a porous media have long been explored in heterogeneous catalysis, such as the percolation model, the stochastic pore network model, and the pore network-continuum model . The fractal geometrical description of the pore networks is given for diffusion-limited aggregation (DLA) clusters, regularly symmetric fractal structures, and statistically symmetric fractal percolating pore networks .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the high surface area of the porous material provides a large number of active sites for formaldehyde adsorption and catalyst loading. Many catalystloaded porous materials or porous transition metal oxides were prepared and displayed excellent formaldehyde oxidation performance; some examples include Pt on ZSM-5 and NaY zeolites, 12,13 mesoporous Au, Pt or Pd/CeO 2 , [14][15][16] VO x /MCM, 17 macro-mesoporous Pt/g-Al 2 O 3 , 18 Pd or Pt/TiO 2 , [19][20][21][22][23][24] Pt/ mesoporous ferrihydrite 25 and porous MnO 2 . 26,27 Various organic templates were used in the preparation of TiO 2 with desired porosity, such as surfactants, 28,29 block copolymers [30][31][32] and even small organic molecules including salicylic acid and aspartic acid.…”
mentioning
confidence: 99%